3D flower-like MnCO3 microcrystals: evolution mechanisms of morphology and enhanced electrochemical performances. (10th October 2017) - Mu, Yanlin; Wang, Li; Zhao, Yan; Liu, Mengjiao; Zhang, Wei; Wu, Jiangtao; Lai, Xin; Fan, Guangyin; Bi, Jian; Gao, Daojiang
Graphical abstract: Schematic illustration for the possible formation mechanism of 3D flower-like MnCO3 microcrystals. Highlights: 3D flower-like MnCO3 microcrystals have been synthesized with the addition of Na3 Cit. The influences of reaction time and dosage of Na3 Cit on the morphology of MnCO3 microcrystals were investigated. A mechanism for the morphology evolution of 3D flower-like MnCO3 microcrystals were proposed. The 3D flower-like MnCO3 microcrystals exhibit the significantly enhanced cycling performance. This work provide valuable insight into the researches on the formation mechanism for inorganic compounds. Abstract: 3D flower-like MnCO3 microcrystals have been prepared via a facile hydrothermal method with the addition of sodium citrate (Na3 Cit). The microstructures of the prepared microcrystals were characterized through X-ray diffraction (XRD), scanning electron microscope (SEM), thermogravimetric analysis (TGA), fourier transform infrared spectroscopy (FTIR) and N2 adsorption. Moreover, a mechanism for the morphology evolution of 3D flower-like MnCO3 microcrystals was also discussed in detail. Using the obtained 3D flower-like MnCO3 microcrystals as anode for lithium ion batteries and a series of tests including charge-discharge test, cycling ability, rate performances, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were carried out. The results show that 3D flower-like MnCO3 microcrystals can be obtained by varying the reaction time and the dosage of Na3 Cit at the hydrothermal temperature of 180 °C, and the suitable hydrothermal reaction time and the dosage of Na3 Cit for the 3D flower-like MnCO3 microcrystals are 12 h and 3 mmol, respectively. The electrochemical measurements indicate that 3D flower-like MnCO3 microcrystals exhibit specific capacity of 384 mAh g −1 at 0.2 C after 200 cycles, showing the significantly enhanced cycling performance than that of the obtained spherical MnCO3 microcrystals.